3-Deoxygalactosone, a new glucose degradation product in peritoneal dialysis fluids: Identification, quantification by HPLC/DAD/MSMS and its pathway of formation - Mittelmaier, Stefan; Fünfrocken, Michael; Fenn, Dominik; Pischetsrieder, Monika (Analytical and Bioanalytical Chemistry, 2011)
Heat sterilization of peritoneal dialysis (PD) fluids leads to the formation of glucose degradation products (GDPs), which considerably impair long-term application of PD. Knowledge of the exact composition of GDPs present in a PD fluid is important to improve the biocompatibility of dialysis solutions. The present study conducted a targeted screening for novel GDPs with α-dicarbonyl structure in PD fluids. Thus, 3-deoxygalactosone (3-DGal) was identified for the first time in PD fluids. Quantification of 3-DGal was achieved by high-performance liquid chromatography (HPLC)/DAD/MSMS after derivatization with o-phenylendiamine to yield the quinoxaline derivative. Baseline separation of all α-dicarbonyl GDPs, particularly of the diastereomers 3-deoxyglucosone (3-DG) and 3-DGal, required the application of a polar, phenyl-based RP column for HPLC and additional pH-gradient elution. Concentrations of 3-DGal ranged between 55.8 and 136.9 μM in single-chamber PD fluids, and between 2.5 and 12.4 μM in double-chamber PD fluids. In solutions containing glucose, 3-DGal is formed from 3-DG via the intermediate 3,4-dideoxyglucosone-3-ene (3,4-DGE). Further studies are now required to determine the (patho-)physiological properties of 3-DGal. © 2010 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.3deoxy
Keywords: 3-Deoxygalactosone (3-DGal); [alpha]-Dicarbonyl compounds; Glucose degradation products (GDPs); HPLC; Peritoneal dialysis fluid; Quinoxaline derivatives

Chemical and physiological relevance of glucose degradation products in peritoneal dialysis - Mittelmaier, Stefan; Niwa, Toshimitsu; Pischetsrieder, Monika (Journal of Renal Nutrition, 2012)
Fibrosis and vascular sclerosis are main complications that limit the long-term application of peritoneal dialysis (PD). Low biocompatibility has been largely attributed to the presence of glucose degradation products (GDPs), which are formed during the heat sterilization of PD fluids. GDPs readily modify proteins in the peritoneum, leading to a decline of their biological function. After absorption, GDPs can also promote systemic protein glycation. Additionally, GDPs may augment DNA glycation, a process enhanced in uremia. Apart from their glycating activity, GDPs induce cytotoxicity and interfere with cell signaling in peritoneal mesothelial cells. Targeted screening revealed the nature of the6major GDPs with α-dicarbonyl structure as 3-deoxyglucosone, 3-deoxygalactosone, glucosone, glyoxal, methylglyoxal, and 3,4-dideoxyglucosone-3-ene. Valid quantification of these GDPs was achieved by ultrahigh-performance liquid chromatography/diode array detector/tandem mass spectrometry. Identification and quantification of single GDPs allow a structure-dependent risk evaluation. As a consequence, PD fluids and processes can be improved to reduce the GDP burden of patients undergoing PD. © 2012 National Kidney Foundation, Inc.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.chemic

Development and validation of an HPLC method to quantify 3,4-dideoxyglucosone-3-ene in peritoneal dialysis fluids - Frischmann, Matthias; Spitzer, Johanna; Fünfrocken, Michael; Mittelmaier, Stefan; Deckert, Melanie; Fichert, Thomas; Pischetsrieder, Monika (Biomedical Chromatography, 2009)
A method was developed and validated to quantify 3,4-dideoxyglucosone-3-ene in peritoneal dialysis fluids by high-performance liquid chromatography with UV detection after derivatization with o-phenylenediamine. The advantages of this method compared with direct HPLC analysis are (i) the possibility of quantifying 3,4-dideoxyglucosone-3-ene simultaneously together with other glucose degradation products, (ii) the compatibility of the method with MS detection for unequivocal identification of the analyte and (iii) a bathochromic shift of the UV absorbance maximum which leads to higher selectivity. The validated method was used to measure 3,4-dideoxyglucosone-3-ene concentrations additionally to the glucose degradation products 3-deoxyglucosone, methylglyoxal, glyoxal, 5-hydroxymethylfurfural, 2-furaldehyde, formaldehyde and acetaldehyde in 19 commercial products for peritoneal dialysis. Copyright © 2009 John Wiley & Sons, Ltd.
UnivIS-Import:2015-04-14:Pub.2009.nat.dchph.llmch.develo
Keywords: 3; 4-Dideoxyglucosone-3-ene (3; 4-DGE); Glucose degradation products (GDP); HPLC; Peritoneal dialysis fluid (PD fluid)

Identification and quantification of six major alpha-dicarbonyl process contaminants in high-fructose corn syrup - Gensberger, Sabrina; Mittelmaier, Stefan; Glomb, Marcus; Pischetsrieder, Monika (Analytical and Bioanalytical Chemistry, 2012)
High-fructose corn syrup (HFCS) is a widely used liquid sweetener produced from corn starch by hydrolysis and partial isomerization of glucose to fructose. During these processing steps, sugars can be considerably degraded, leading, for example, to the formation of reactive aα- dicarbonyl compounds (aα-DCs). The present study performed targeted screening to identify the major aα-DCs in HFCS. For this purpose, aα-DCs were selectively converted with o-phenylendiamine to the corresponding quinoxaline derivatives, which were analyzed by liquid chromatography with hyphenated diode array-tandem mass spectrometry (LC-DAD-MS/MS) detection. 3-Deoxy-D-erythro-hexos-2- ulose (3-deoxyglucosone), D-lyxo-hexos-2-ulose (glucosone), 3-deoxy-D-threo-hexos-2- ulose (3-deoxygalactosone), 1-deoxy-D-erythro-hexos-2,3-diulose (1- deoxyglucosone), 3,4-dideoxyglucosone-3-ene, methylglyoxal, and glyoxal were identified by enhanced mass spectra as well as MS/MS product ion spectra using the synthesized standards as reference. Addition of diethylene triamine pentaacetic acid and adjustment of the derivatization conditions ensured complete derivatization without de novo formation for all identified aα-DCs in HFCS matrix except for glyoxal. Subsequently, a ultra-high performance LC-DAD-MS/MS method was established to quantify 3- deoxyglucosone, glucosone, 3-deoxygalactosone, 1- deoxyglucosone, 3,4-dideoxyglucosone-3-ene, and methylglyoxal in HFCS. Depending on the aα-DC compound and concentration, the recovery ranged between 89.2% and 105.8% with a relative standard deviation between 1.9% and 6.5%. Subsequently, the aα-DC profiles of 14 commercial HFCS samples were recorded. 3-Deoxyglucosone was identified as the major aα-DC with concentrations up to 730 μg/mL HFCS. The total aα-DC content ranged from 293 μg/mL to 1,130 μg/mL HFCS. Significantly different aα-DC levels were not detected between different HFCS specifications, but between samples of various manufacturers indicating that the aα-DC load is influenced by the production procedures. © 2012 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.identi
Keywords: α-Dicarbonyl compound (α-DC); High-fructose corn syrup (HFCS); o-Phenylenediamine (OPD); Quinoxaline derivatives; Sugar degradation products; Ultra high-performance liquid chromatography (UHPLC)

Identification and quantification of the glucose degradation product glucosone in peritoneal dialysis fluids by HPLC/DAD/MSMS - Mittelmaier, Stefan; Fünfrocken, Michael; Fenn, Dominik; Fichert, Thomas; Pischetsrieder, Monika (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2010)
Glucose degradation products (GDPs) formed during heat sterilization of peritoneal dialysis (PD) fluids exert cytotoxic effects and promote the formation of advanced glycation end-products in the peritoneal cavity. As a result, long-term application of continuous ambulatory peritoneal dialysis is limited. The composition and concentration of GDPs in PD fluids must be known to evaluate their biological effects. The present study describes a targeted screening for novel GDPs in PD fluids. For this purpose, dicarbonyl compounds were converted with o-phenylenediamine to give the respective quinoxaline derivatives, which were selectively monitored by HPLC/diode array detector. Glucosone was thereby identified as a novel major GDP in PD fluids. Product identity was confirmed by LC/MSMS analysis using independently synthesized glucosone as a reference compound. Furthermore, a method was developed to quantify glucosone in PD fluids by HPLC/UV after derivatization with o-phenylenediamine. The method's limit of detection was 0.6 μM and the limit of quantitation 1.1 μM. A linear calibration curve was obtained between 1.1 and 113.9 μM (R2 = 0.9999). Analyzed at three different concentration levels, recovery varied between 95.6% and 102.0%. The coefficient of variation ranged between 0.4% and 4.7%. The method was then applied to the measurement of glucosone in typical PD fluids. Glucosone levels in double chamber bag PD fluids varied between not detectable and 6.7 μM. In single chamber bag fluids, glucosone levels ranged between 28.7 and 40.7 μM. © 2010 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dchph.llmch.identi_4
Keywords: [alpha]-Dicarbonyl compounds; Glucose degradation products (GDPs); Glucosone; HPLC; Peritoneal dialysis fluid; Quinoxaline derivatives

Multistep ultrahigh performance liquid chromatography/tandem mass spectrometry analysis for untargeted quantification of glycating activity and identification of most relevant glycation products - Mittelmaier, Stefan; Pischetsrieder, Monika (Analytical Chemistry, 2011)
The use of advanced glycation end-products (AGEs) as biomarkers for diagnosis and clinical studies is still hampered by insufficient knowledge on clinically relevant structures formed from precursors associated with defined disease states. The present study conducted untargeted analysis of the glycating activity of AGE-precursors by ultrahigh performance liquid chromatography/ tandem mass spectrometry multiple reaction monitoring (UHPLC/MSMS-MRM), monitoring the loss of a nonapeptide as the glycation target. Thus, the glycating activities of seven important AGE-precursors were determined (glucose 13% and the reactive carbonyl compounds glucosone 39%, 3-deoxyglucosone 15%, 3-deoxygalactosone 26%, 3,4-dideoxyglucosone-3-ene 79%, methylglyoxal 94%, and glyoxal 97% peptide loss; 12 h/37 °C). Furthermore, UHPLC/MSMS with simultaneous precursor ion scan and information-dependent acquisition of enhanced resolution spectra and subsequent product ion scan was applied for untargeted analysis of the major AGE-structures derived from various AGE-precursors. The 20 most important modifications could be assigned to 8 AGE-structures previously reported in the literature. Seven loosely bound AGEs not yet covered by conventional methods were detected and assigned to hemiaminals. Five AGE structures did not match any known products. The method can be applied to analyze glycating activity and AGE-structures formed from various other precursors under defined reaction conditions, supporting the selection and evaluation of diagnostic AGE-markers for clinical studies. © 2011 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.multis

Quantification of the six major alpha-dicarbonyl contaminants in peritoneal dialysis fluids by UHPLC/DAD/MSMS - Mittelmaier, Stefan; Fünfrocken, Michael; Fenn, Dominik; Berlich, Robert; Pischetsrieder, Monika (Analytical and Bioanalytical Chemistry, 2011)
During heat sterilization of peritoneal dialysis solutions, glucose is partially transformed into glucose degradation products (GDPs), which significantly reduce the biocompatibility of these medicinal products. Targeted α-dicarbonyl screening identified glyoxal, methylglyoxal, 3-deoxyglucosone, 3,4-dideooxyglucosone-3-ene, glucosone, and 3-deoxygalactosone as the major six GDPs with α-dicarbonyl structure. In the present study, an ultra-high-performance liquid chromatography method was developed which allows the separation of all relevant α-dicarbonyl GDPs within a run time of 15 min after derivatization with o-phenylenediamine. Hyphenated diode array detection/tandem mass spectrometry detection provides very robust quantification and, at the same time, unequivocal peak confirmation. Systematic evaluation of the derivatization process resulted in an optimal derivatization period that provided maximal derivatization yield, minimal de novo formation (uncertainty range ±5%), and maximal sample throughput. The limit of detection of the method ranged from 0.13 to 0.19 μM and the limit of quantification from 0.40 to 0.57 μM. Relative standard deviations were below 5%, and recovery rates ranged between 91% and 154%, dependent on the type and concentration of the analyte (in 87 out of 90 samples, recovery rates were 100∈±∈ 15%). The method was then applied for the analysis of commercial peritoneal dialysis fluids (nine different product types, samples from three lots of each). [Figure not available: see fulltext.] © 2011 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.quanti
Keywords: α-Dicarbonyl compounds; 3; 4-DGE; Glucose degradation products; Peritoneal dialysis fluids; Tandem mass spectrometry; UHPLC